Shakemap and Focal Mechanism Analysis of the December 2024 Gresik Earthquake - Mochamad Tanwiruz Zaman; Agus Suprianto; Lutfi Rohman; Bowo Eko Cahyono (Program Studi Fisika Universitas Negeri Jakarta, 2026)
An earthquake that occurred on December 30, 2024 in Gresik Regency, located at 7.05° S and 112.62° E with a focal depth of 14 km and magnitude M3.3, was a shallow earthquake felt with an intensity of II–III MMI. This study aims to analyze the earthquake shaking intensity map (Shakemap), determine the earthquake source mechanism, and perform earthquake scenario modeling using the maximum magnitude based on the Indonesian Earthquake Source and Hazard Map (PUSGEN). Shakemap analysis was carried out using the BMKG Shakemap server based on accelerograph network data. Fault mechanism analysis was performed using focal mechanism software with P-wave polarity input obtained from waveform signal picking using SeisGram2K software. Meanwhile, the Shakemap scenario was generated using the ShakeMap application available at the Pasuruan Geophysical Station. The results show that the distribution of Peak Ground Acceleration (PGA) and shaking intensity is influenced not only by the distance from the epicenter but also by local geological conditions that contribute to ground-motion amplification. Source mechanism analysis indicates that the Gresik earthquake was dominated by a strike-slip faulting mechanism with a weak oblique component, interpreted as sinistral strike-slip motion along the RMKS–Tuban 3 fault zone. Scenario earthquake modeling with a magnitude of M 6.2 indicates that Gresik Regency has the potential to experience strong ground shaking with maximum intensities reaching VI–VII MMI, while surrounding areas such as Surabaya City, eastern Lamongan Regency, and western Bangkalan Regency may experience intensities up to VI MMI. These findings indicate that although the Gresik earthquake had a relatively small magnitude, the potential earthquake impact in Gresik and surrounding areas could become significant if a maximum-magnitude earthquake occurs, therefore, this study provides important information for earthquake disaster mitigation efforts.